Nitric oxide modifies photosynthetic electron transport in pea leaves - Wodala, Barnabás (Acta Biologica Szegediensis, 2005)
Previous electron paramagnetic resonance (EPR) and chlorophyll a fluorescence studies on isolated thylakoid membranes showed that nitric oxide (NO), a transmembrane messenger gaseous free radical, slows down the rate of photosynthetic electron transport in vitro. NO could reversibly bind to several sites of photosystem II (PS II) (e.g. non-heme iron complex between QA and QB, QB binding site, water-oxidizing complex) by replacing bicarbonate and causes an inhibitory effect on photophosphorylation. Our results show that in vivo application of NO by several specific NO donor molecules slowed down the rate of QA-reoxidation in pea leaves. NO reduced the optimal quantum efficiency by increasing the dark fluorescence yield (Fo) and decreasing the variable fluorescence (Fv). It also decreased the photochemical quenching (qP) and modified the non-photochemical (NPQ), mainly energy-dependent quenching (qE) in a concentration related manner. Dark relaxation of NPQ also showed, that NO enlarged the photoinhibitory quenching. Since NO acts as a signalling molecule in plant cells during various stresses, our results predict that NO, in a nanomolar concentration range, can assist to avoid the potential stress induced photodamage by inducing heat dissipation of excess light in the PS II antenna. In contrast, higher, cytotoxic concentrations, NO serves as a photosynthetic inhibitor.